THE RELATIONSHIP OF SOCIAL SUPPORT WITH RESILIENCE IN PAUD TEACHERS - Sitti Anggraini; Maria Rinalti Dua Monika (Sean Institute, 2023)
This study aims to examine the relationship between social support and resilience in PAUD teachers in Magepanda district. The subjects in this study were PAUD teachers in Magepanda District with a total of 60 people. The sampling technique in this study was a saturated sample (census), ie the entire population was sampled. This research method uses quantitative correlation research by collecting data using the academic resilience scale and social support scale. So that the results of the hypothesis test were obtained with a correlation index of 0.754 with a significant level of (p) 0.000 <0.05, which means that there is a positive relationship between social support and the resilience of PAUD teachers in Magepanda sub-district, meaning that the higher the social support for PAUD teachers, the higher the resilience. for PAUD teachers and vice versa, the higher the resilience of PAUD teachers, the higher the social support for PAUD teachers.